Chapter Lodovico Nocentini: A Rereader of Modern Italian Travellers to China - De Angeli, Aglaia (Connessioni. Studies in Transcultural History, 2022)
In 1882, Nocentini published Il primo sinologo: P. Matteo Ricci. The first secular biography of the famous Italian Jesuit to China, it posed important questions about the origins of sinology and the role of Matteo Ricci as an early modern Italian traveller in Sino-western relations. Nocentini's rereading of Matteo Ricci and travel literature in Italy in the late nineteenth century is examined through theories proposed by Derrida, Barthes and Nabokov. These theories provide an interpretative approach to understand the rereading carried out in Nocentini's work, as they are intended as a process of interpretation and reinterpretation, as well as appropriation of the original meaning.